Consumption of Traditional Fruits and Vegetables among Children in the US-Affiliated Pacific Region. Issue 7 (16th June 2022) - Dela Cruz, Rica; Wolfe, Eric; Yonemori, Kim M; Fialkowski, Marie K; Wilkens, Lynne R; Coleman, Patricia; Lameko-Mua, Sunema; Johnson, Emihner; Gilmatam, Daisy; Sigrah, Cecilia; Shomour, Moria; Remengesau, Shelley; et al.
ABSTRACT: Background: Traditional Pacific diets have many health benefits, including maintenance of a healthy weight and prevention of various diseases. Few studies have evaluated the frequency at which traditional diets are consumed in the Pacific, especially among children. Objectives: This study examined the frequency of traditional and acculturated fruit and vegetable (F&V) intake among children in the US-affiliated Pacific (USAP) region. Methods: Diet records of 3319 children ages 2 to 8 y old were analyzed for frequency of traditional or acculturated F&V intake within USAP jurisdictions of American Samoa, Commonwealth of the Northern Mariana Islands (CNMI), Federated States of Micronesia (FSM; FSM island states include Chuuk, Kosrae, Pohnpei, and Yap), Guam, Hawaii, Republic of the Marshall Islands (RMI), and Republic of Palau. Results: Of the 95, 304 food items recorded among participating children in the USAP jurisdictions, 15.2% were F&Vs. Of the 10 jurisdictions, children in the islands of Chuuk, Kosrae, Yap, and Pohnpei recorded the highest frequencies of traditional F&V intake relative to their total F&V intake (67.8%, 64.8%, 56.7%, and 52.5%, respectively). American Samoa and RMI recorded moderate frequency of traditional F&V intake (38.9% and 46.4%, respectively), whereas children in Hawaii, Guam, and CNMI recorded the lowest frequencies of traditional F&V intake relative to their total F&V intake (10.4%, 12.4%, and 15.3%, respectively). Children in Hawaii, Guam, Palau, and CNMI recorded high frequencies of acculturated F&V intake (37.8%, 31.2%, 34.5%, and 27.9%, respectively). Conclusions: Overall, children in the USAP jurisdictions participating in this study recorded a low frequency of F&V intake. The differences in traditional F&V intake found between the USAP islands may be due to variation in economic income level and external influences on social and cultural norms among the island populations and variations of cost, accessibility, and convenience of each category of food to each island's population. Abstract : Among 3319 children, aged 2–8 y, residing in 10 jurisdictions of the US-affiliated Pacific region, only 27.8% of the fruits and vegetables eaten were considered traditional foods.